The role of community participation and community empowerment in the planning and delivery of low-income housing : an evaluation of housing project 59 in Paarl - Oosthuizen, Jolandie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MS en S)--Stellenbosch University, 2003.